If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(12y + -11) = -4(1 + -6y) Reorder the terms: 2(-11 + 12y) = -4(1 + -6y) (-11 * 2 + 12y * 2) = -4(1 + -6y) (-22 + 24y) = -4(1 + -6y) -22 + 24y = (1 * -4 + -6y * -4) -22 + 24y = (-4 + 24y) Add '-24y' to each side of the equation. -22 + 24y + -24y = -4 + 24y + -24y Combine like terms: 24y + -24y = 0 -22 + 0 = -4 + 24y + -24y -22 = -4 + 24y + -24y Combine like terms: 24y + -24y = 0 -22 = -4 + 0 -22 = -4 Solving -22 = -4 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| -(x-8)+4=2(12)+x | | 25=10+5j | | 5m^2+26m+5=0 | | 2x-3*-13=9 | | -(x-8)+4=2(-12)+x | | 7x+3(5-3x)=5 | | b+3+b=b+50 | | ly-8l+6=15 | | 3a+1=a+19 | | 15.08+w=30.08 | | Cosx/cos^2(2x) | | -5x-3*-13=30 | | 7m+48=8(m+7) | | 3b^2+11b+8=0 | | -5x-(3*-13)=30 | | 18=5-2+6x-x | | -(x-8)+4=2(7)+x | | x+14=35 | | (r-p)/(x-q)=m | | -5x-(-3*-13)=30 | | 2x-4-6=0 | | 12+[6+(13-7)]2-5= | | 72/4.8=20.4/c | | -(x-8)+4=2(-1)+x | | y+4.3=5.9 | | 42x^2-40x+8=0 | | 5k^2+35k+60=0 | | -(x-8)+4=2(1.25)+x | | 12/x=7/3 | | -(x-8)+4=2(0)+x | | 3(2p+7)=1 | | 7/n=24.5/56 |